Komparasi Tingkat Pemenuhan Kebutuhan Pokok Rumah Tangga Transmigran Dan Rumah Tangga Masyarakat Lokaldi Kecamatan Lunang Kabupaten Pesisir Selatan (Studi Kasus Nagari Lunang Satu Dan Nagari Pondok Parian Lunang) - Afri Yusmawardi; Ratna Wilis (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
Abstrack The purposes of this research are to compare and describe the welfare levels of transmigrants and local communities about the ability to meet food, clothing, shelter and doing education in Lunang Sub-district, Pesisir Selatan Regency. The type of this research is descriptive quantitative. The sample are 56 transmigrantrespondents 22 local community respondents . The technique of sampling respondents is using random sampling. Research data collection with questionnaires and data analysis techniques is using percentage formulas and Likert scales. The results of the study indicate that: ( 1) the ability to fulfill domestic food in transmigrantare moderate and in the local communitiesare low , ( 2) the ability to provide home clothing transmigrant stairs are high and house stairs local communities are low , ( 3) the ability to provide house boards stairs transmigrant are high and house stairs the local communitiesare moderate , ( 4) the ability to carry out home education transmigrant stairs are high and the local community ladder is low. In conclusion, the level of welfare of the transmigrant community is classified as prosperous while the local communities are not yet prosperous, there are still many families who are classified as poor and unable.